Pengaruh Edukasi 3M Plus dengan Media Leaflet Bahasa Madura Terhadap Perilaku Pencegahan DBD di Kabupaten Probolinggo - Munir, Zainal (Jurnal Keperawatan Profesional, 2023)
Dengue Hemorrhagic Fever (DHF) is a public health problem in Indonesia, because the number of sufferers and the area of its spread is increasing along with increasing mobility and population density (Kemenkes RI, 2010). Aedes aegypti hemorrhagic fever, characterized by a sudden high fever accompanied by bleeding manifestations and tends to cause shock and death. Dengue (DHF) is an infectious disease by the dengue virus that is transmitted through mosquito bites.Research Methods : The design used in this study was a Quasi Experiment research design using a pretest-posttest design with control group. The sampling technique used in this study was probability sampling with a total sampling method of 73 respondents, namely 37 intervention groups and 36 control groups. Analysis of the data in this study using the paired T-Test.Research Results : Shows the effect of 3M Plus education with Madura leaflet media on dengue prevention behavior in intervention group respondents with Asymp 0.000 <α = 0.05. Ha accepted. Thus it can be concluded that there is a significant difference between before and after being given education about 3M Plus and Javanese language leaflet media on dengue prevention behavior in the Karanganyar Paiton Probolinggo.Conclusion: There is an Influence of 3M Plus Education Using Javanese Language Leaflet Media on DHF Prevention Behavior at Karanganyar Paiton Probolinggo.